The lexicon-syntax interface in second language aquisition - Hout, Roeland van (Language acquisition & language disorders, 2003)
Second language acquisition has to integrate the totality of the SLA process, which includes both the learning of the core syntax of a language and the learning of the lexical items that have to be incorporated into that syntax. But these two domains involve different kinds of learning. Syntax is learnt through a process of implementing a particular set of universal structures, whereas the learning of lexis is characterised by the building up of associations (or connections). Yet these two systems must come together in the creation of a whole linguistic system in the mind of an individual. Thi.